Raw material planning for tapioca flour production based on fuzzy logic approach: a case study - Santosa, Sesar Husen; Hidayat, Agung Prayudha; Siskandar, Ridwan (Universitas Serang Raya, 2022)
The availability of cassava raw materials influences tapioca flour production at small and medium industry's (SMIs) Bogor Regency. Cassava raw material is a crucial factor in producing cassava yields, affecting the amount of tapioca flour production. Planning for cassava raw material must be carried out properly because the quality and quantity of cassava must be maintained to achieve the tapioca flour production target. The results of forecasting the demand for tapioca flour in SMIs using the Multiplicative Decomposition method were 2566 kg with MAD = 173.73 and MAPE = 0.08. Based on the analysis of the effectiveness of the grinding machine, the average value of OEE for one year is 0.32 (32%). Based on the value of demand forecasting results, milling machine OEE and tapioca flour prices, an analysis of cassava raw material needs are carried out using a fuzzy logic approach. The membership set used is Triangular and Trapezoidal Membership Function and Fuzzy Rule Base as many as 81 possibilities. The defuzzification of cassava raw material requirements in SMIs is 17600 kg. Based on the results of defuzzification, the need for raw materials must be increased so that the demand for tapioca flour can be achieved.